YEVGENY M. TAREEV – A MAN, WHO HAD BEEN AHEAD OF THE TIME IN MEDICAL SCIENCE (INTERVIEW WITH ACADEMICIAN N.A. MUKHIN) - N. V. Dolgushina (Рациональная фармакотерапия в кардиологии, 2015)
Yevgeny M. Tareev – a man, who had been ahead of the time in medical science (interview with Academician N.A. Mukhin).